Úvěrování podnikatele vybranými bankovními a nebankovními institucemi - Václavík, Lukáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2018)
Bakalářská práce se zabývá porovnáním možností úvěrování podnikatelského subjektu podnikatelským úvěrem u vybraných bankovních a nebankovních institucí. Jednotlivé možnosti jsou mezi sebou porovnány na základě analýzy nabídek od vybraných institucí s působností na českém finančním trhu dle preferencí managementu podniku. Pro podnik budou doporučeny nejvhodnější varianty externího financování.

The bachelor thesis deals with the comparison of the possibilities of lending entrepreneurial subject by business credit by selected banking and non-banking institutions. The individual options are compared on the basis of the analysis of offers from selected institutions with competence on the Czech financial market according to the preferences of the company management. The most suitable external financing options will be recommended for the company.
Borrowing the Entrepreneur by Selected Banking and Non-banking Institutions
Keywords: úvěr; podnikatelský úvěr; bankovní instituce; nebankovní instituce; rpsn; komparace; credit; business credit; banking institutions; non-banking institutions; rpsn; comparison